Comparative In Vitro Cytotoxicity Study of Carbon Dot-Based Organometallic Nanoconjugates: Exploration of Their Cell Proliferation, Uptake, and Localization in Cancerous and Normal Cells. (15th March 2022) - Priyadarshini, Eepsita; Meena, Ramovatar; Bohidar, Himadri B.; Sharma, Saurabh Kumar; Abdellattif, Magda H.; Saravanan, Muthupandian; Rajamani, Paulraj
Abstract : Organometallic nanoconjugates have raised great interest due to their bimodal properties and high stability. In the present study, we analyzed the cytotoxicity property of carbon dots (CDs) and a series of organometallic nanoconjugates including gold@carbon dots (Au@CDs) and silver@carbon dots (Ag@CDs) synthesized via an aqueous mode. We aimed to divulge a comparative analysis of cell proliferation, uptake, and localization of the particles in HeLa and HEK293 cell lines. Our results showed dose-dependent cytotoxicity of Au@CDs, Ag@CDs, and CDs. However, Ag@CDs showed the highest inhibition through HeLa cells with an IC50 value of around 50 ± 1.0   μ g/mL. Confocal imaging signified the uptake of the particles suggested by blue fluorescence in the interior region of HeLa cells. Furthermore, the TEM micrographs depicted that the particles are entrapped by endocytosis assisted through the cell microvilli. The CDs and Au@CDs were thus observed to be relatively safe up to a concentration of 100  μ g/mL and did not induce any morphological changes in the cells. Moreover, the cell proliferation assay of these nanoconjugates against HEK 293 cells signified the nontoxic nature of the nanoconjugates. The results thus revealed two major facts: firstly, the Ag@CDs had potent therapeutic potential, signifying their potential as a promising anticancer drug, and secondly, the CDs and Au@CDs at a defined dose could be used as probes for detection and also bioimaging agents.